E-supply chain technologies and management - Zhang, Qingyu, 1970- (Hershey, PA : Information Science Reference, 2007)
"This book explores concepts, models, and IT infrastructures of the e-supply chain, and develops a broad understanding of issues pertaining to the use of emerging technologies and their impact on supply chain flexibility and management. It provides key ideas, concepts and applications suited to guide efforts in transforming current business processes to adapt to the digital age"--Provided by publisher.
Ηλεκτρονικό βιβλίο
Keywords: Business logistics -- Technological innovations; Information technology; Electronic books